Is traditional perinatal autopsy needed after detailed fetal ultrasound and post‐mortem MRI?. (15th April 2019) - Shelmerdine, Susan C.; Arthurs, Owen J.; Gilpin, Isobel; Norman, Wendy; Jones, Rod; Taylor, Andrew M.; Sebire, Neil J.; Chitty, Lyn S.
Abstract: Objective: To determine the additional yield from autopsy following prenatal ultrasound and post‐mortem magnetic resonance imaging (PMMR) for structural abnormalities. Method: PMMR was performed on consecutive fetuses over a 6‐year period. Prenatal ultrasound and PMMR findings were categorised as concordant, partially concordant or discordant findings. The yield of new and clinically significant information from autopsy was assessed. Diagnostic accuracies for both modalities were calculated, using autopsy as reference standard. Results: Our study consisted of 81 fetuses. PMMR and prenatal ultrasound findings were concordant in 44/81 (54.3%), partially concordant in 26/81 (32.1%) and discordant in 11/81 (13.6%) cases. In 19/81 cases (23%), autopsy provided additional information, which appeared clinically significant in 12 cases. In 10 of those 12 cases, there was discordance between PMMR and ultrasound. In only 2 of 44 cases where ultrasound and PMMR were concordant, did autopsy provide clinically significant information. Diagnostic accuracy rates for ultrasound were sensitivity of 76.8% (66.6%, 84.6%), specificity of 92.5% (88.9%, 95.0%). For PMMR the sensitivity was 79.0% (68.9%, 86.5%), specificity 97.9% (95.5%, 99.0%). PMMR had a significantly higher concordance rate with autopsy than ultrasound (89.0 vs 93.8%; P  < .001). Conclusion: Where PMMR and ultrasound are concordant, there is little additional yield from autopsy. Abstract : What is already known about this topic? Prenatal ultrasound and post‐mortem MRI provide good diagnostic accuracy for major congenital anomalies. Whilst traditional perinatal autopsy remains the reference standard investigation, many parents decline this invasive procedure. What does this study add? Where prenatal ultrasound and PMMR imaging are concordant, there is little additional benefit from invasive autopsy. The highest yield from autopsy is when findings from the imaging modalities are discordant. Post‐mortem MRI may help triage cases that would benefit most from an invasive autopsy.